Communication Model of Assistance of Village Owned Business Entity in Muna Barat District - Zulfiah Larisu; La Tarifu; Sumadi Dilla; Jopang Jopang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine effective communication model for Bumdes assistance in West Muna district. The method used in this research is descriptive with a qualitative approach. The results of this study indicate that the communication of BUMDes Mentoring in West Muna Regency is carried out intensely, both between BUMDes Facilitators and BUMDes Management, Village Government and village communities. Communication Barriers BUMDes assistance was found to be generally physical, technical or geographical. An effective communication model in BUMdes Mentoring is found to be a model that applies the clarity of the communication process from the communicator, messages, media, communicants and the resulting effects. Therefore, the two-way discussion and dialogue model dominates the effective communication model in BUMDes Assistance.